Synchronicity in international stock markets: evidence from USA-South Africa. (1st January 2014) - Lakshmi, P.; Visalakshmi, S.; Shanmugam, Kavitha
The South African equity market witnessed very strong lift since 1994 and is included in BRICS countries in 2010. The emergence of the sub-prime crisis in the USA had an adverse impact on the global markets especially emerging market like South Africa. The primary objective of the present study is to analyse the distinctiveness of price movements and volatility spill over effects between the USA (NYSE) and the emerging economy of South Africa employing daily time series data spanning Jun 2006 to May 2012. The stock price synchronicity is examined using VECM-based causal relationship during the 2006–2012 (entire sample period) and 2007–2009 (financial crisis period). Further, the speed of transmission of shocks from the USA to SA in the long run, short run deviations and swiftness of recovery during the US subprime mortgage crisis is also analysed. The results reveal that both long-run and short-run dynamic nexus exist between these stock markets. In addition, the nexus is amplified in the short-run during the US financial crisis. This suggests that changes in the US stock markets swiftly affect the South African stock market and the US index acts as a conducing indicator for information transmission across the two markets.